A System of Labelling on Simple Bottles and Cans Using the Method of Computer Graphics - AGUI, Takeshi; NAKAJIMA, Masayuki; INOUE, Masao (Bulletin of the Technical Association of Graphic Arts of Japan, 1985)
Many CAD systems for package designing of various industrial goods and daily use utensils have been studied and developed. In this paper, a system of labelling on simple bottles and cans is described. This CAD system is an application of computer graphics on packaging as labelling, in which texture mapping is used to treat rather complicated three-dimensional objects. A labelling system for bodies of revolution is described, and examples of color pictures formed on the display are shown.